2021
DOI: 10.1111/ddi.13289
|View full text |Cite
|
Sign up to set email alerts
|

Golden mussel (Limnoperna fortunei) survival during winter at the northern invasion front implies a potential high‐latitude distribution

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 58 publications
(141 reference statements)
1
12
0
Order By: Relevance
“…This provides validation for our hypothesis (Zhan et al, 2015). Xia, Barker, et al (2021) found that golden mussels could survive the cold winter in areas covering the entire SNWDP. This suggests that established populations can produce propagules during the warm months that then may disperse to new locations.…”
Section: Discussionmentioning
confidence: 99%
“…This provides validation for our hypothesis (Zhan et al, 2015). Xia, Barker, et al (2021) found that golden mussels could survive the cold winter in areas covering the entire SNWDP. This suggests that established populations can produce propagules during the warm months that then may disperse to new locations.…”
Section: Discussionmentioning
confidence: 99%
“…Reproductive capacity and tolerance to extreme environmental conditions also facilitate the invasion of new habitats by L. fortunei (GIGLIO, 2016). Furthermore, L. fortunei has high tolerance to low temperatures, which may contribute to its invasion success (XIA et al, 2021).…”
Section: Limnoperna Fortunei the Golden Musselmentioning
confidence: 99%
“…Shortly after the commencement of the MRSNWDP, a substantial number of golden mussels, encompassing larvae and adults, were discovered along the water transfer channels [ 10 , 12 ]. This occurrence is attributed to the presence of the golden mussels within the Danjiangkou Reservoir, which acts as the source for their invasion from southern to northern regions of China [ 10 , 15 ]. Notably, the rapid invasion of mussels in water transfer projects extends beyond the MRSNWDP and encompasses other endeavors such as the Dongjiang Water Source Diversion Project in China [ 16 ].…”
Section: Introductionmentioning
confidence: 99%